2015
DOI: 10.1007/s11748-015-0587-y
|View full text |Cite
|
Sign up to set email alerts
|

Robotic resection of a mediastinal parathyroid cyst

Abstract: Mediastinal parathyroid cysts (PC) are rare, benign lesions, reported in fewer than 150 cases worldwide. Although most are asymptomatic and discovered incidentally on imaging, symptoms of dyspnea, dysphagia, hoarseness, palpitations, hypercalcemia, and innominate or jugular venous thrombosis have been reported. Sternotomy or thoracotomy has traditionally been the approach used to resect mediastinal PCs. We describe the first reported case of a robot-assisted resection of a mediastinal PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The optimal surgical approach depends on the location and size of the cyst, as well as the individual experience of surgeons. Go et al reported a robotic resection of an MPC of 4.5 h, using four arms of the da Vinci Si system with two assistant ports 9 . In order to facilitate the operation, the patient twice underwent endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) and a total of 520 ml of fluid was aspirated from the cyst 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The optimal surgical approach depends on the location and size of the cyst, as well as the individual experience of surgeons. Go et al reported a robotic resection of an MPC of 4.5 h, using four arms of the da Vinci Si system with two assistant ports 9 . In order to facilitate the operation, the patient twice underwent endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) and a total of 520 ml of fluid was aspirated from the cyst 9 .…”
Section: Discussionmentioning
confidence: 99%
“…[2] Functioning mediastinal parathyroid cysts of the mediastinum are easy to diagnose due to the presence of symptoms of hyperparathyroidism and an evidence of mediastinal cysts. However, non-functioning mediastinal parathyroid cysts, which are seen in up to 60 to 80% of cases, are usually diagnosed incidentally and most commonly following the surgical excision.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, video-assisted thoracoscopic surgery, robotic surgery, and the use of intraoperative gamma probe scanning have come into question. [2] Furthermore, lately, it has been reported that robotic surgery is an effective and safe procedure for benign mediastinal lesions. [8] Total excision of the cyst is considered a curative treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classically accessed via cervical anterior approach, sternotomy, or thoracotomy, video-assisted thoracoscopic surgery (VATS) is now the mainstay of therapy for these surgically challenging lesions; however, the recent introduction of robotic surgery offers an alternative approach with distinct advantages (7)(8)(9)(10)(12)(13)(14)(15). The literature includes several reports of robotically resected mediastinal adenomas and cysts; however, to our knowledge, this is the first report of a robotically resected intrathymic functional PC (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%